Early Determinants of Intergenerational Upward and Downward Educational Mobility - Markus P. Neuenschwander; Lukas Ramseier; Ariana Garrote (Education Sciences)
Intergenerational educational mobility means that adolescents graduate at a higher level (upward mobility) or lower level (downward mobility) than their parents did. Knowledge about early determinants supports upward and downward mobility at an early stage. Evidence about early determinants of educational mobility allows for the elaboration of educational strategies to minimize the correlation between family socio-economic status (SES) and student upper-secondary education level. In this longitudinal study (N = 2376), we examined the extent to which teacher and parent expectations in 7th grade (mean age: 13.2 years) predict the achievement and effort of adolescents with and without migration backgrounds and the probability of upward and downward mobility at the end of upper-secondary education. The results showed indirect effects of teacher and parent expectations on upward and downward mobility, mediated by student achievement, after controlling for gender and conscientiousness. The effects of parent expectations were stronger than the effects of teacher expectations. Effort predicted downward mobility more than achievement in mathematics and German. No differences were found between adolescents with and without migration backgrounds. In the case of the tracked Swiss education system, parents’ and teacher expectations predicted educational mobility over long periods.